Meaningful-Experience Creation and Event Management A Post-Event Analysis of Copenhagen Carnival 2009 - Sarah Holst Kjær (Culture Unbound: Journal of Current Cultural Research, 2011)
A carnival is a cultural event within the experience economy, and can be considered an activity of added value to a city when creating place-awareness for tourists and residents. ‘Culture’ is used as a way to regenerate post-industrial and run down places, when studying EU – as well as Nordic – cultural policy reports. This might be too much to expect from the cultural sector though. Amongst other external factors, cultural policy ideals co-create and affect the experiential content of an event in various ways. Thus studying a carnival one has to include external and internal factors in order to evaluate their meaningfulness in the total experience of the event. One way to investigate what a meaningful experience is can be to apply a cultural consumer perspective. How different consumer segments directly and indirectly inform the event organisation and how the consumer’s cultural preconceptions judge the event is vital when an event organisation designs and improves its experience concepts and experience setting. Thus, the way the carnival’s venue and activities are culturally received is closely linked to the management of the organisation’s external and internal resources. The goal of an event organisation is to produce meaningful and appealing experience concepts and perform them in real time. But how is this organised in practice? This article evaluates the production of the Copenhagen Carnival 2009 and is based on ethnographic material. Through a model of Value Framework for Experience Production by the Dutch experience economists Albert Boswijk, Thomas Thijssen & Ed Peelen (2007) I analyse how the practical organisation, technical solutions and cultural assumptions of a carnival are part of an event organisation’s work-process when creating a spectacle. Furthermore, the organisation of voluntary professional culture workers and the navigation in a metropolitan, political and institutional context is examined through the management concepts of routine, creativity and co-creation.